Water sorption isotherms of cooked hams as affected by temperature and chemical composition - Barretto, Tiago Luis; Polachini, Tiago Carregari; Barretto, Andrea Carla Da Silva; Telis-romero, Javier (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2018)
AbstractThis study was focused on the determination of the chemical composition and experimentally obtaining the sorption isotherms for four samples of commercial cooked ham subjected to simulated commercial storage conditions. The isotherms were determined using the gravimetric method. The mathematical models of Guggenhein, Anderson and de Boer; Brunauer, Emmett and Teller; Halsey; Henderson; and Peleg were fitted to the experimental data. The Guggenhein, Anderson and de Boer model was chosen to best describe the isotherms as it had a very good fit. The increase in temperature reduced the equilibrium moisture content of the product. Increased relative humidity resulted in an increase in equilibrium moisture content of the product regardless of storage temperature. The differences in chemical composition between the samples affect the desorption isotherms. The higher the content and availability of the protein or the lower the fat content, the higher the equilibrium moisture content of the product.
Keywords: mathematical modelling; equilibrium moisture content; water activity; protein; fat